Influence of polypropylene fiber length and geometric shape on the compressive strength of cemented lepidolite tailings backfill - Zuo, Liping; Huang, Nanhui; Wang, Genwei; Zhu, Daopei (Frontiers in Materials, 2024)
Lepidolite ore contains abundant lithium resources; however, the extraction process generates a large number of tailings, which are environmentally hazardous solid waste. Currently, cemented fiber reinforcement and tailings filling technologies are commonly used methods for tailings treatment. The fiber length and geometric shape significantly affect the performance of fiberreinforced cemented lepidolite tailing backfill (CLTB). However, there is limited research on the impact of these two factors on the performance of CLTB. Consequently, Polypropylene fiberreinforced CLTB of four sizes and four fiber lengths were prepared and used for uniaxial compressive strength (UCS) tests. The max UCS of fiber-reinforced CLTB was 2.84MPa, and the maximum increase percent was 83.7% compared with the non-fiber-reinforced CLTB. The experimental results show that when the fiber length was 12 mm the CLTB had the maximum UCS, longer fibers did not necessarily result in a higher UCS. The end effect was significant when the difference in cross-sectional area was small. The UCS of the L-40 sample was higher than that of the Y-50 sample under the same fiber length. The differences in the size effect and geometric shape were the main factors influencing their mechanical performance. When the fiber length was from 0 mm to 6 mm, the size effect was obvious, the UCS values gradually decreased with an increase in the volume ratio and cross-sectional area. However, the fiber length was the primary factor influencing the fitting curve of the UCS when the fiber length was from 12 mm to 19 mm.Additionally, the addition of fibers enhanced the integrity of CLTB. In other words, fiber-reinforced CLTB exhibited improving structural integrity. This study reflects the CLTB performance under the action of different sizes and different fiber lengths, improving the filling efficiency, mining, and backfill safety.This study can provide theoretical references for the research and practical applications of fiber-reinforced fillers and size effects, as well as the treatment of lepidolite tailings, while also reflecting the CLTB performance under the action of different sizes and different fiber lengths, improving the filling efficiency, mining, and backfill safety.